2017
DOI: 10.2147/jir.s128292
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-induced autophagy and ferritin degradation contribute to epithelial–mesenchymal transition through lysosomal iron

Abstract: PurposeTransforming growth factor (TGF)-β1 triggers epithelial–mesenchymal transition (EMT) through autophagy, which is partly driven by reactive oxygen species (ROS). The aim of this study was to determine whether leaking lysosomes and enhanced degradation of H-ferritin could be involved in EMT and whether it could be possible to prevent EMT by iron chelation targeting of the lysosome.Materials and methodsEMT, H-ferritin, and autophagy were evaluated in TGF-β1-stimulated A549 human lung epithelial cells cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
(93 reference statements)
0
16
1
Order By: Relevance
“…Normally, NCOA4 acts as a transcriptional coactivator of several nuclear receptors, and its additional function was recently identified as an inhibitor in the activation of DNA replication origins [48]; the downregulation of snail, slug, and vimentin in DpdtCtreated cells might be due to the upregulation of NCOA4. In addition, it has been shown that ROS involved TGF-β1induced EMT, and the decrease of ferritin heavy chain (FHC) contributed to EMT transition [49][50][51]. However, the ferritin degradation induced by DpdtC achieved EMT inhibition in our study; the difference might be attributed to a difference in manner of ferritin downregulation achieved; the knockdown of ferritin by sh-RNA was at translation level, while induced ferritinophagy by DpdtC at posttranslation modification.…”
Section: Discussioncontrasting
confidence: 55%
“…Normally, NCOA4 acts as a transcriptional coactivator of several nuclear receptors, and its additional function was recently identified as an inhibitor in the activation of DNA replication origins [48]; the downregulation of snail, slug, and vimentin in DpdtCtreated cells might be due to the upregulation of NCOA4. In addition, it has been shown that ROS involved TGF-β1induced EMT, and the decrease of ferritin heavy chain (FHC) contributed to EMT transition [49][50][51]. However, the ferritin degradation induced by DpdtC achieved EMT inhibition in our study; the difference might be attributed to a difference in manner of ferritin downregulation achieved; the knockdown of ferritin by sh-RNA was at translation level, while induced ferritinophagy by DpdtC at posttranslation modification.…”
Section: Discussioncontrasting
confidence: 55%
“…Recent studies in non-CNS cells have demonstrated that EMT can occur with activation of autophagy stimulated by reactive oxygen species [48]. We found that expression of two EMT markers were increased in ALS motor neurons, vimentin (ALS/CTL = 2.6) and N-cadherin (CDH2, ALS/CTL = 2.9).…”
Section: Discussionmentioning
confidence: 73%
“…In terms of additional investigations, it might be worthwhile to pursue the possibility that the "prolonged autophagic death" described by Martin [49] and increased autophagy markers in sporadic ALS MN's described by Sasaki [45] might arise as a result of oxidative stress-driven autophagy [48] through activation of epithelial-mesenchymal transition (EMT) of motor neurons. EMT is not known to occur normally in non-malignant tissues except during developmental neuronal polarization and migration [50], amniotic membrane rupture [51], organ fibrosis [52] and cardiac cells in culture [53].…”
Section: Limitations Of Gene Expressionmentioning
confidence: 99%
“…Ferritin synthesis is stimulated during the development and cell differentiation, inflammation, and tumorigenesis. A decrease in H-ferritin can induce epithelial-to-mesenchymal transition of mammalian tumor cells through the TGF-β1 pathway [12][13][14]. Hypoxia inducible factor A (HIFA) can directly bind with hypoxia response element (HRE) in the promoter region of human L-ferritin (HuLF) to enhance its expression thus regulating epithelial-to-mesenchymal transition of glioma [15].…”
Section: Introductionmentioning
confidence: 99%